2013
DOI: 10.1007/s00216-012-6700-5
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic speciation in saliva of acute promyelocytic leukemia patients undergoing arsenic trioxide treatment

Abstract: Arsenic trioxide has been successfully used as a therapeutic in the treatment of acute promyelocytic leukemia (APL). Detailed monitoring of the therapeutic arsenic and its metabolites in various accessible specimens of APL patients can contribute to improving treatment efficacy and minimizing arsenic-induced side effects. This article focuses on the determination of arsenic species in saliva samples from APL patients undergoing arsenic treatment. Saliva samples were collected from nine APL patients over three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Although the methylated species are the primary products excreted in urine, their trivalent forms (i.e., MMA III and DMA III ) are intrinsically more toxic than As III , with the pentavalent species themselves being generally nontoxic at experimental levels relevant to human environmental exposure (Aposhian et al, 2003). Notably, arsenic trioxide (As 2 O 3 ) is used clinically as a highly effective treatment of acute promyelocytic leukemia and is converted to As III and, subsequently, to methylated species in vivo after administration (Chen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Although the methylated species are the primary products excreted in urine, their trivalent forms (i.e., MMA III and DMA III ) are intrinsically more toxic than As III , with the pentavalent species themselves being generally nontoxic at experimental levels relevant to human environmental exposure (Aposhian et al, 2003). Notably, arsenic trioxide (As 2 O 3 ) is used clinically as a highly effective treatment of acute promyelocytic leukemia and is converted to As III and, subsequently, to methylated species in vivo after administration (Chen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In a different study, Chen et al [27] analysed the arsenic speciation in the saliva of acute promyelocytic leukaemia (APL) patients undergoing arsenic trioxide treatment and suggested that saliva could be used as an appropriate clinical biomarker for monitoring arsenic species in APL patients. However, all of the previous studies mainly focused on the detection of arsenic and its species in the saliva of humans exposed to inorganic arsenicals.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, arsenicals excreted via enterohepatic circulation might be transformed by gastrointestinal microbiota into thiolated arsenicals, which were then absorbed into the bloodstream and finally excreted into the urine . However, microbial production was not considered as the only source of thio-containing arsenicals because these arsenicals were also found in the liver of rats that received portal intravenous injection of DMA V , DMA III , MMA V , or MMA III , and in the saliva of acute promyelocytic leukemia patients undertaking intravenous infusion of iAs III . , The conversion of DMMTA V into DMDTA V was also observed in the incubation with rat RBCs . These results implied that some biological reactions in the organisms also could contribute to the formation of thio-containing arsenicals.…”
Section: Resultsmentioning
confidence: 99%
“…An Agilent 1100 series HPLC system that comprised a pump, degasser, autosampler, column temperature control, and reversed-phase C18 column (ODS-3, 150 mm × 4.6 mm, 3-μm particle size; Phenomenex, Torrance, CA, USA) was used for the separation of arsenicals. 27 An octadecylsilane guard cartridge (4 mm × 3 mm) was mounted before the analytical column. The mobile phase consisted of 5 mM tetrabutylammonium, 5% methanol, and 3 mM malonic acid (pH 5.65).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation